(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The Office of the Comptroller General of the State, in Ecuadorian territory, is the institution in charge of controlling state resources administered by public servants. For this purpose, it is essential to have the professional service of external and internal auditors who, through audits, guarantee the aforementioned control. The objective of this manuscript is to analyze the disciplinary responsibilities that concern the auditor in the professional exercise and that make it possible to evaluate his ethical and professional behavior; through a documentary research, with a qualitative approach and ethnographic design. Using the interview to collect information from external auditors working in the Office of the Comptroller General of the State of the province of Esmeraldas. The results obtained in this research show that in the exercise of the public function, it is a priority to comply with the legal precepts established in the national legal framework; therefore, the government auditor must guide his work under principles and values that regulate his actions and conduct; comply with the duties and prohibitions assigned in the position; in such a way that compliance with the assigned disciplinary responsibilities strengthens confidence in the auditing profession, guarantees the reliability of the financial information and avoids incurring in disciplinary sanctions caused by action or omission that affect the normal development of their attributions.